2016
DOI: 10.1021/acs.jpcb.6b02712
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genome in the Formation of Conical Retroviral Shells

Abstract: Human immunodeficiency virus (HIV) capsid proteins spontaneously assemble around the genome into a protective protein shell called the capsid, which can take on a variety of shapes broadly classified as conical, cylindrical and irregular. The majority of capsids seen in in vivo studies are conical in shape, while in vitro experiments have shown a preference for cylindrical capsids. The factors involved in the selection of the unique shape of HIV capsids are not well understood, and in particular the impact of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…= D[ψ(r)]e − 1 2 υ drψ 2 (r) e −iυ N 0 ds ψ(r(s)) , (19) with ψ the auxiliary field representing the monomer density field. Plugging Eqs.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…= D[ψ(r)]e − 1 2 υ drψ 2 (r) e −iυ N 0 ds ψ(r(s)) , (19) with ψ the auxiliary field representing the monomer density field. Plugging Eqs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Indeed, it appears that the compactness of the ssRNA wild-type viral genomes is one of the principal characteristics of their nucleotide sequence, setting them distinctly apart from randomized sequences [11,19], and that the physical compactness of the viral genome can be regarded as a primary factor among evolutionary constraints [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein-protein interactions between CA domains are the driving force for Gag assembly in the immature hexagonal lattice 4,5 as well as for CA assembly in the mature capsid [6][7][8] . Previous computer simulations and theoretical studies have revealed key features of CA self-assembly into conical mature HIV-1 capsids [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on synthetic polyions and nanoparticles find Q is between 0.6 and 9, depending on the molecular weight, topology of the polyanion and so on [ 30 , 55 , 56 ]. Recently, we argued that the value of Q should depend on the level of (annealed) branching, the linear charge density and the quality of the solvent of the polyanion [ 8 , 32 , 49 , 50 , 52 ]. In the next section, we make it plausible that in addition Q may well depend on the concentration of the polyanion too.…”
Section: Cargo Length and Encapsulation Efficiencymentioning
confidence: 99%